Call of the wild: Creating a formal wilderness medicine elective for Canadian pre-clerkship medical students - Omand, Geordon; Gourlay, Katie; Zeeman, Michael; Pietrosanu, Matthew; Jerome, David (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Implication StatementWilderness medicine education is interesting to medical students, yet not widely implemented in Canadian medical curricula. We describe a curriculum for a pre-clerkship wilderness medicine elective at a Canadian medical school. Our study reports increased student awareness of career opportunities in wilderness medicine after elective completion, and interest in hands-on learning for wilderness medicine topics. Medical schools may benefit from incorporating feedback from our elective towards a successful wilderness medicine curriculum in their own programs.